Dressing for employment females applying into creative and conservative industries - Lopez, Kathleen Mae C.
It only takes about three minutes to make a first impression that will impact you for maybe about your entire lifetime (Satran, 1990). So the first three minutes in a pre-employment situation are the most critical because you get but one chance for a good first impression. Before you can utter your first word, your appearance has already spoken volumes about you. While it does not speak of your job skills, your appearance, judged in some respects by what you wear, may contribute to the probability of being hired. Therefore, your clothing should not only make you feel good about yourself but also project a professional image matching the requirements of the position and the company (Damhorst et al, 1999). This is a descriptive cross-sectional study of the appropriate female attire for job interviews in the context of the Philippine setting. This study aimed to determine whether the applicant's attire has an effect on her chances of selection. The appropriate attire was described in terms of garment style, silhouette and color based on what respondents from conservative and creative industries deemed appropriate. Employment interviewers from the different companies in Metro Manila was selected through a purposive sampling procedure and were asked to answer an on-line questionnaire for this purpose. The results of the survey have been tallied and presented in textual and tabular form. From the results and data gathered, it is evident that applicant attire is a contributing factor to selection. The company's criteria for appropriate attire are influenced by its image, culture, the job position open, the nature of the job and the work environment. Apart from the clothes, the applicant's hairstyle, kind of shoes, the use of stockings, application of make-up, choice of accessories and general grooming should also be carefully decided upon. Modesty and simplicity should be reflected in the attire worn by sticking to the use of long-sleeved tops and suits, knee-length skirts, long pants, and clothes with minimal design details and a natural silhouette. Neutral colors are most preferred. Appropriate attire was determined separately for creative industries and conservative industries. The chi square test was performed to validate the differences in the results. Based on the chi-square test, there is no association between the type of industry applied into and the appropriate attire to be worn. Accordingly, the researcher suggests that further studies be made to validate the association, using a larger sample for more reliable results.